Palinología del Cuaternario del Iberá, provincia de Corrientes. - Anzótegui, Luisa Matilde (2004)
One of the aims of the paleopalinology is to reconstruct the vegetation history, climate and environments of the past. Pallinological studies in the Ituzaingó Formation, that outcrops in Corrientes Province, show that an ecotone existed during the Pliocene, connecting the phytogeographic provinces Paranaense (with hygrophilous forests and aquatic plants) sand Chaqueña (with xerophytic forests), both typical of subtropical South America with some migration of species. The swamp and shallow lake system from Iberá, occupies a central position in the Corrientes Province, following a NE-SO direction, with a surface of about 12.000 km2. The thick, peat-like deposits locally called “embalsados” that characterize these swamps, were formed during the Holocene, but showed scarce pollen preservation in previous studies (just in the first meter depth, decreasing through the base). However, sediment corers obtained in the bottom of small lakes, show abundant pollen content with good preservation, thus increasing the chances of obtaining better paleovegetation, climatic and environmental information from the Late Quaternary of the region